Implementing a Target-Task Problem-Solving Model in teaching Electrochemistry to Advanced level chemistry learners. - Mandina, Shadreck; Dube, Eshiwet (Birlesik Dunya Yenilik Arastirma ve Yayıncilik Merkezi, 2021)
The study investigated the effect of a Target-Task Approach on the performance of advanced level chemistry students in electrochemistry. The study adopted the quasi-experimental research design. Data were obtained from two advanced level chemistry classes from two high schools in Gweru, Zimbabwe. One of the two classes was assigned to be the experimental group, while the other class acted as the control group. The experimental group was taught electrochemistry using Target-Task Approach, while the conventional method was used to teach the control group. Analysis of covariance was used to analyse all the data generated from the study. The hypotheses formulated were all tested at the 5% level of significance. The results revealed that the difference in performance between the experimental and control group was statistically significant. The findings further show that the use of the Target-Task Approach greatly enhance the performance of low and medium scoring level students.